BERNYANYI DENGAN NADA YANG BENAR DAN TEPAT MENINGKATKAN KEMAMPUAN OLAH RASA MUSIKAL - Andre Suharto (JURNAL PENDIDIKAN DASAR, 2015)
Abstract: The purity and precisely of tone are the most important elements of the musics beauty. The music aesthetics is abstract. Every tone has its own characteristic. Every student also has different ability toward each other. Therefore, the realm of learning material should be combined with the students ability. The ability limitation and difficulty during the learning process could be solved through the disciplines, so that in the end the student can sing with the right and precise according the music aesthetics.Keyword: The purity and precisely of tone, The music aesthetics.Abstrak: Kemurnian dan ketepatan nada adalah unsur penting keindahan music. Estetika music bersifat abstrak. Tiap nada memiliki sifat sendiri. Tiap siswa juga memiliki kemampuan berbeda satu sama lainnya. Ranah materi pembelajaran harus dipadukan dengan kemampuan siswa. Pengalaman menunjukkan bahwa estetika musik dapat dipelajari. Dengan disiplin, keterbatasan kemampuan dan tingkat kesulitan dapat diatasi, sehingga pelajar dapat bernyanyi dengan benar dan tepat sesuai dengan estetika musik.Kata kunci: kemurnian dan ketepatan nada, estetika musik.